Karakteristik Audit Eksternal dan Skala Perusahaan sebagai Determinan Penghindaran Pajak: Bukti Empiris dari Indonesia - Anugrah Dwi Oktavian; Made Dudy Satyawan (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Although Indonesia's nominal tax revenues have grown annually, the tax-to-GDP ratio remains persistently below international benchmarks, partly due to corporate tax avoidance. This study examines how public accounting firm (KAP) size, audit fees, and company scale influence tax avoidance among non-financial companies listed on the Indonesia Stock Exchange over 2020–2024. Agency Theory and Political Cost Theory serve as the theoretical foundation, arguing that external monitoring intensity and corporate public visibility jointly shape managerial incentives regarding tax obligations. A balanced panel of 115 non-financial firms yielding 575 firm-year observations was constructed through purposive sampling. Estimation using the Fixed Effect Model with Robust Standard Errors in Stata 17 produces three findings: KAP size has no statistically significant effect on tax avoidance, suggesting that standardized audit protocols neutralize size-based quality differences between Big Four and non-Big Four firms; audit fees show a significant negative effect, indicating that higher monitoring expenditure constrains aggressive tax planning; and firm size similarly produces a significant negative effect, consistent with the prediction that larger firms face greater regulatory scrutiny discouraging tax aggressiveness. These findings offer practical guidance for policymakers seeking to leverage audit mechanisms as instruments of corporate tax compliance.